Insights into the interaction of potent antimicrobial chalcone triazole analogs with human serum albumin: spectroscopy and molecular docking approaches. Issue 55 (8th October 2019) - Yadav, Priyanka; Yadav, Jitendra Kumar; Agarwal, Alka; Awasthi, Satish K.
Abstract : Mechanistic insights into the interaction of five previously chemically synthesized triazole-linked chalcone analogs with human serum albumin were analyzed using UV-visible absorption, fluorescence quenching, circular dichroism and molecular docking studies. Abstract : Mechanistic insights into the interaction of five previously chemically synthesized triazole-linked chalcone analogs (CTs) with human serum albumin (HSA) were sought using various spectroscopic techniques (UV-visible absorption, fluorescence, and circular dichroism) and molecular docking. The fluorescence quenching experiments performed at three different temperatures (288, 298 and 308 K) revealed the static mode of quenching and the binding constants ( K b ∼ 10 6–9 ) obtained indicated the strong affinity of these analogs for HSA. Furthermore, significant changes in the secondary structure of HSA in the presence of these analogs were also confirmed by far UV-CD spectroscopy. The thermodynamic properties such as the enthalpy change (Δ H °), Gibbs free energy change (Δ G °) and entropy change (Δ S °) revealed that the binding process was spontaneous and exothermic. Theoretical studies, viz., DFT and molecular docking corroborated the experimental results as these five analogs could bind with HSA through hydrogen bonding and hydrophobic interactions. The present study provides useful information regarding the interaction mechanism of these analogs with HSA, which can provide a new avenue to design more potent chalcone triazole analogs for use in the biomedical field.